2021
DOI: 10.1007/s10668-020-01173-3
|View full text |Cite
|
Sign up to set email alerts
|

Microfiber pollution: an ongoing major environmental issue related to the sustainable development of textile and clothing industry

Abstract: Textiles release microfibers to the environment during production, use, and at end-of-life disposal. There is a potentially large and growing risk to the environment associated with microfiber pollution, which requires protection and sustainable development in the textile and fashion industry. To date, early-stage research efforts, perhaps the most important initial actions to explore more feasible and effective solutions, into microfiber pollution from the perspective of environmental sustainability have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…Fibers accounted for more than 92% of the MP and 73% of that were found to be polyester having the same size and color as those found in garments (Ross et al 2021). The reduced microfiber density (Brahney et al 2020) can make them more transportable over a long range by water and wind (Liu et al 2021) and their high surface to volume ratio can bind more noxious contaminants, potentially making them more dangerous to the aquatic species that other forms of microplastics (Liu et al 2019). A large proportion of microfiber can slip out of treatment plants owing to their limited size and get discharged into marine habitats (Napper and Thompson 2016).…”
Section: Current Studies On Microplastic Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibers accounted for more than 92% of the MP and 73% of that were found to be polyester having the same size and color as those found in garments (Ross et al 2021). The reduced microfiber density (Brahney et al 2020) can make them more transportable over a long range by water and wind (Liu et al 2021) and their high surface to volume ratio can bind more noxious contaminants, potentially making them more dangerous to the aquatic species that other forms of microplastics (Liu et al 2019). A large proportion of microfiber can slip out of treatment plants owing to their limited size and get discharged into marine habitats (Napper and Thompson 2016).…”
Section: Current Studies On Microplastic Pollutionmentioning
confidence: 99%
“…A recent study (Ross et al 2021) found that the Arctic is rampantly contaminated by MP fibers that would possibly come from the laundering of clothes. Because of the increase in textile manufacturing and the lack of microfiber deterioration, aggregation of microfibers will become more extreme (Liu et al 2021). In 96 out of 97 samples collected from around the arctic ocean, the most detailed analysis to date has detected microplastics.…”
Section: Current Studies On Microplastic Pollutionmentioning
confidence: 99%
“…Microfibres can be generated by fragmentation of textile fibres with or without exposure to solar UV radiation. Textile production processes [192][193][194][195] that involve abrasion [196] and electric dryers [197] as well as domestic laundering of clothes [198][199][200] mechanically generate microfibres in wastewater that reaches the ocean. However, the exposure of fabric to solar UV radiation also contributes to their degradation and fragmentation.…”
Section: Synthetic Microfibre Fragments Generated By Mechanical or De...mentioning
confidence: 99%
“…Many adverse effects have been identified as hundreds of contaminants are diluted in aquatic systems, affecting dissolved oxygen, turbidity, color, temperature, and, consequently, marine organisms. In this regard, the potential relationship between effluent toxicity and chemical oxygen demand has been discussed by [16].…”
Section: Synthetic Color Effect To the Environmentmentioning
confidence: 99%